STRATEGI GERAKAN CIVIL ISLAM DALAM MERESPON BENCANA GEMPA BUMI DI SULAWESI BARAT - Choirunnisa; Hendy Setiawan; Arissy Jorgi Sutan; Wihda Maulani Maulani (JUSTICE: Journal of Social and Political Science, 2022)
Disasters are complex issues that cannot be handled by a single actor. Even the government with all the resources at its disposal will not be able to solve disaster problems without involving networks and organizations outside the country. Therefor networking and collaboration are the keys to how to respond to disasters quickly and accurately so that the recovery process can occur quickly. In addition, responding to disasters requires a constructive strategy so that in overcoming disasters, it does not exacerbate the impact of the disaster.  The purpose of this article is to explore how Muhammadiyah's strategy as a civil Islam responds to the earthquake that occurred in West Sulawesi. The reason is because Muhammadiyah in responding to the disaster in West Sulawesi is an example of how its resources are optimally mobilized to solve the problem of the earthquake in West Sulawesi. Starting from the involvement of institutions such as MDMC, PWM, PDM, LazizMu, educational institutions, hospitals, social fields and others. It is of course very interesting to review how Muhammadiyah has provided support for the movement in responding to disasters as a call for a humanitarian mission that has long been inflated. This research method uses a qualitative approach and descriptive methods and in collecting data the author uses report data from Muhammadiyah, media, journals, news, or other literature. Research results show that Muhammadiyah's strategy is very effective for the recovery of disaster victims in West Sulawesi. This cannot be separated from how in the Muhammadiyah strategy, it has the strength of solidity, coordination, and networks that support and strengthen each other so that the organization between institutions is very successful.